Economics of COVID-19: challenges and the way forward for health policy during and after the pandemic - Shankar Prinja; Chandrakant S Pandav (Wolters Kluwer Medknow Publications, 2020)
The emergence of novel coronavirus disease 2019 (COVID-19) pandemic provides unique challenges for health system. While on the one hand, the government has to struggle with the strategies for control of COVID-19, on the other hand, other routine health services also need to be managed. Second, the infrastructure needs to be augmented to meet the potential epidemic surge of cases. Third, economic welfare and household income need to be guaranteed. All of these have complicated the routine ways in which the governments have dealt with various trade-offs to determine the health and public policies. In this paper, we outline key economic principles for the government to consider for policymaking, during, and after the COVID-19 pandemic. The pandemic rightfully places long due attention of policymakers for investing in health sector. The policy entrepreneurs and public health community should not miss this once-in-a-lifetime "policy window" to raise the level of advocacy for appropriate investment in health sector.